Analysis of the Role of Legal Education and Community Welfare on Social Justice and Human Rights in Rural Areas in Central Java - Loso Judijanto; Shohib Muslim; Sabil Mokodenseho; Nana Rolina Masloman; Tindra Manangin (West Science Social and Humanities Studies, 2024)
This qualitative research delves into the dynamic intersection of legal education, community welfare, social justice, and human rights in rural areas of Central Java, Indonesia. Through in-depth interviews, focus group discussions, and thematic analysis using NVivo software, the study explores the perceptions, experiences, and practices of stakeholders involved in initiatives aimed at promoting social justice and human rights. Key themes that emerged include the importance of legal literacy in enhancing awareness of rights, challenges in accessing justice, the transformative impact of empowerment and participation, the need for holistic approaches that address intersecting social challenges, and the vital role of collaboration and networking among diverse stakeholders. The findings shed light on the complexities and opportunities inherent in promoting social justice and human rights in rural contexts, providing valuable insights for the development of inclusive and sustainable interventions.